Case of the Whitechapel vampire - Gibbons, Rodney; Frewer, Matt, 1958-; Welsh, Kenneth; Doyle, Arthur Conan, 1859-1930.; Hallmark Entertainment (Firm); MUSE Film and Television; Platinum Disc Corporation (La Crosse, WI : Platinum Disc, 2005)
A fly-by-night killer is leaving Sherlock Holmes in the dark.
Originally produced for television 2002.
Based on the characters created by Sir Arthur Conan Doyle.
Written and directed by Rodney Gibbons.
Matt Frewer, Kenneth Welsh.
DVD, full screen presentation; Dolby surround sound.
112920
Keywords: Holmes, Sherlock -- Drama; Murder -- Investigation -- Drama; Homicide -- Investigation -- Drama; Sherlock Holmes films; Mystery; Detective and mystery films; Detective and mystery television programs; Drama; Made-for-TV movies